Regulatory solutions to bank loans procyclicality: Is the cure worse than the illness? - Verónica Balzarotti; Alejandra Anastasi (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2010)
The impact of the business cycle on banks' internally generated cash flow is an important driver in the pro-cyclical dynamics of the traditional banking business and yet the issue has been understated in the discussion on counter-cyclical regulations. Considerable attention has been given to the need to lessen capital scarcity during the downturns and to the discrepancy between accounting rules and regulation standpoints. In contrast, the importance of incentives arising from this type of regulations has received little attention. We develop an exercise of a representative bank to illustrate the dynamic effects of some counter-cyclical regulatory schemes, with a special focus on the impact on cash flows. We show that while a counter-cyclical provisioning scheme changes the temporal impact of the cycle on accounting earnings, it may still stress cyclicality. Alternative counter-cyclical regulatory schemes such as time-varying capital and liquidity requirements are also assessed with a focus on the above mentioned impact on cash flows and other potential drawbacks associated with the interplay among accounting rules, signaling and incentives to 'manage the balance sheet'.
Keywords: E32; G21; G28; 330; banking system; bank loans; counter-cyclical regulation; procyclicality; Bankenliquidität; Cash Flow; Bilanzstrukturmanagement; Konjunktur